Thermally activated viscoelasticity of cement paste: Minute-long creep tests and micromechanical link to molecular properties. (January 2023) - Binder, Eva; Königsberger, Markus; Díaz Flores, Rodrigo; Mang, Herbert A.; Hellmich, Christian; Pichler, Bernhard L.A.
Abstract: The stiffness of cementitious materials decreases with increasing temperature. Herein, macroscopic samples of mature cement pastes are subjected at 20, 30, and 45 °C, respectively, to three-minutes-long creep compression experiments. The test evaluation is based on the linear theory of viscoelasticity and Boltzmann's superposition principle. This yields macroscopic elastic and creep moduli as a function of temperature. A state-of-the-art multiscale model for creep homogenization of cement paste is extended to account for temperature-dependent elastic and creep moduli of the hydrate gel. This extension is based on results from published molecular simulations. Temperature-independent stiffness is assumed for cement clinker. Upscaling to the macroscale of cement paste yields elastic and creep moduli which agree well with the aforementioned experimental results. The Arrhenius-type activation energy of the creep modulus is found to be independent of scale, composition, and maturity, because of ineffective stress redistributions from creeping to non-creeping constituents. Highlights: Three-minutes creep tests of mature cement paste are performed at 20, 30, and 45 °C. They give access to elastic and creep moduli rooted in linear viscoelasticity. A multiscale model links these moduli to MD results at the hydrate level. Across the scales, the activation energy of creep equals that of water.